Do voleibol ao minivoleibol para surdos: um estudo histórico da modalidade praticada por surdos na região de Santa Maria/RS - Souza, Maria Esther Gomes de (2024)
This dissertation sought to answer the research problem: how Volleyball and Minivolleyball for the Deaf developed in the Santa Maria Region. The methodological procedures adopted include a bibliographical review, with works of deaf researchers, collection of information through reports, social networks and electronic websites with information from the Association of the Deaf of Santa Maria/RS (ASSM) and the development of Volleyball and Minivolleyball for the Deaf in the region. The results highlighted the importance of Brazilian Sign Language as a cultural artifact for the deaf community and sports as places for cultural exchange and spaces for strengthening the deaf community. The organization of Volleyball and Minivolleyball for the Deaf, from 2018 to 2024, proved to be a potentiator of ASSM, bringing benefits reflected in organizational evolution, participation in events and having been included with PROESP from 2022. The practice of Minivolleyball for the Deaf, using Libras and adapted spaces, increased the number of participants in tournaments, which ended up drawing the attention of the Rio Grande do Sul Sports Federation of the Deaf (FDSRS) which recognized the practice as a modality and has held State Minivolleyball Championships for the Deaf since 2022, mentioned in the interviews and proven by photographs. The interviews with the leaders also show that the deaf are individuals who work together as a community, with the deaf community in the region being the main protagonist in the evolution and expansion of the practice of Volleyball and Minivolleyball for the Deaf from Santa Maria/RS. This work opens the possibility for future studies on the topic, mainly deepening the methodological aspects of teaching Volleyball and Minivolleyball for the Deaf